2019
DOI: 10.1158/1535-7163.mct-18-0365
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Novel Therapies and Targets: Regulation of Notch3 by the Bromodomain Protein BRD4

Abstract: Systematic approaches for accurate repurposing of targeted therapies are needed. We developed and aimed to biologically validate our therapy predicting tool (TPT) for the repurposing of targeted therapies for specific tumor types by testing the role of Bromodomain and Extra-Terminal motif inhibitors (BETi) in inhibiting BRD4 function and downregulating Notch3 signaling in ovarian cancer.Utilizing established ovarian cancer preclinical models, we carried out in vitro and in vivo studies with clinically relevant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…We previously reported that CN210 potently inhibited bromodomains of BET proteins with K d values ranging from 11 nM to 200 nM [17, 28]. In the present study, we demonstrated that CN210 also inhibited the bromodomains of two paralogous HATs, CBP and p300, with K d values of 260 nM and 190 nM, respectively (Table 1) as compared to the previously reported K d values of 70 nM for BRD4 [17].…”
Section: Resultssupporting
confidence: 68%
“…We previously reported that CN210 potently inhibited bromodomains of BET proteins with K d values ranging from 11 nM to 200 nM [17, 28]. In the present study, we demonstrated that CN210 also inhibited the bromodomains of two paralogous HATs, CBP and p300, with K d values of 260 nM and 190 nM, respectively (Table 1) as compared to the previously reported K d values of 70 nM for BRD4 [17].…”
Section: Resultssupporting
confidence: 68%
“…Targeted treatments and immunohistochemistry offer the hope of improved treatments for OC patients in the future. Moreover, identifying biomarkers for targeted treatments is important for effective cancer diagnosis and treatment ( Shivange et al, 2018 ; Villar-Prados et al, 2018 ). RNA sequencing is an accurate method used to identify such biomarkers ( Coenen-Stass et al, 2018 ; Jiang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The targeted treatment of OC plays an increasingly important role in the comprehensive treatment of OC and new tumor treatment strategies depend on the search for new targets ( Huang et al, 2018 ; Shivange et al, 2018 ; Villar-Prados et al, 2018 ; Zhai et al, 2018 ). With the development of sequencing technology and acquirement of a large amount of biological data, bioinformatics can be used to understand and find new biomarkers of tumor ( Yang et al, 2020 ; Wu et al, 2019 ; Tao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, NSD3-BRD4-CHD8 pathway functions in pelvic high-grade serous carcinomas originated from tubo-ovarian and endometrial [33]. Of note, BRD4 is predicted as a novel therapeutic target for regulating Notch3 signaling in OC [34]. Also, MiR-3619-5p inhibits cell proliferation and cisplatin resistance in cutaneous squamous cell cancer by targeting KPNA4 [35].…”
Section: Discussionmentioning
confidence: 99%